GAME DESIGN AS LEARNING MEDIA OF ENGLISH PRONUNCIATION USING SET COLLECTION MECHANICS - Timothy, Jonathan Andrian; Prasida, Tan Arie Setiawan; Prestilliano, Jasson (Universitas Pendidikan Ganesha, 2020)
English is an official language used to communicate between countries. Indonesia also learns English that can be learned from elementary school or kindergarten. However, pronunciation or pronunciation still bears serious mispronunciation, both vocalization, emphasis, and overall. Reliance on English has complexity and technique that the Bahasa pronunciation does not have. The problem with research is strategy and developing of a board game to learn English - speaking techniques. The purpose of this research is to design a learning media of English pronunciation through board game. This research uses experimental methods, linear strategies and combination approaches. The sources for this study are studies, books, interviews with professors and students. This research is about learning pronunciation using board game as a media. The purpose of this study is to design a game board called the Word Detector as a learning media. The result of this study is an increase in the result of the learning process performed before, after and several days after playing a board of games